Characterization and priming of equine muscle-derived mesenchymal stem cells to enhance their anti-inflammatory and immunomodulatory profiles - Shahid, Muhammad A.; Guitart, Albert Sole; Bertin, François-René; Simon, Olivier; Ceusters, Justine; Serteyn, Didier; Whitworth, Deanne J. (Frontiers in Veterinary Science, 2026)
A minimally invasive microbiopsy-based method for the isolation of mesenchymal stem cells (MSCs) from equine skeletal muscle (M-MSCs) provides a readily accessible source of MSCs for clinical applications. We examined the expression of genes associated with immunomodulation and anti-inflammatory pathways, in addition to those of growth factors and the major histocompatibility complex (MHC) molecules I and II, at constitutive levels and after priming with inflammatory cytokines, an immunostimulant, and heat-shocking. While there was notable variation between the M-MSCs from each of the horses in their constitutive expression of many of the genes examined, and in their responses to the different priming methods, priming with TNF-α and IFN-γ increased the expression of genes associated with anti-inflammatory pathways, immunomodulation, and tissue repair. M-MSCs from all horses constitutively expressed MHC-I and lacked expression of MHC-II; only heat-shocking induced the expression of MHC-II. The responses to priming, together with their ease of harvesting, supports further investigation into the use of M-MSCs as a therapy for inflammatory and immune-mediated conditions in the horse. However, due to the variability between M-MSCs from different individuals, characterization of the cells before autologous administration, and the selection of those cells most fit-for-purpose in the case of allogeneic transfer, is recommended.